Programming with types : examples in TypeScript - Riscutia, Vlad (Manning Publications, 2020)
Containing numerous examples, applications, and scenarios that you will encounter in your day job, this book teaches you type system techniques for writing software that's safe, correct, easy to test and maintain, and that practically documents itself. --